Comparison of the effects of inhalation anesthetics in the intraand postoperative periods during kidney transplantation - N. K. Kuznetsova; V. E. Aleksandrova; I. I. Utkina; A. M. Talyzin; S. V. Zhuravel (Трансплантология (Москва), 2020)
Background. Every year the number of patients with chronic renal failure is steadily increasing. Allogeneic kidney transplantation from a post-mortem donor is a radical method to cope with chronic renal failure, improving the quality and life expectancy of patients. Currently available inhalation anesthetics make it easy to control the depth of anesthesia; they are excreted by the lungs unchanged, providing a quick emergence from anesthesia and easy waking up of the patient. An “ideal” inhalation anesthetic used for kidney transplantation should have a minimal amount of adverse effects.The aim was to compare the efficacy of inhaled anesthetics used for allogeneic kidney transplantation from a posthumous donor.Material and methods. A randomized, prospective, single-center study included 62 patients with end-stage chronic renal failure. The subjects were divided into three groups depending on the type of the inhalation anesthetic used. The first group included patients who underwent low-flow inhalation anesthesia with desflurane, the second and third groups were comparator groups where patients received sevoflurane or isoflurane, respectively, as an inhalation anesthetic. When assessing hemodynamic parameters, most episodes of hemodynamic instability were seen in the isoflurane group; the most stable statistically significant values were observed in the sevoflurane group, and desflurane took an intermediate position.Results. The use of desflurane as an inhalation anesthetic in a kidney transplant provided a quicker recovery of consciousness and early extubation of the patient after anesthesia compared to the sevoflurane or isoflurane use. So desflurane proved to be the most efficient of the three studied inhalation anesthetics. Conclusion. Desflurane is the optimal inhalation anesthetic used in kidney transplantation.